PENGARUH PERBEDAAN DOSIS PAKAN IKAN RUCAH TERHADAP PERTUMBUHAN IKAN KARDINAL BANGGAI (Pterapogon kauderni) - Saruni; Sulystyaningsih, Naning Dwi; Hamid; Muahiddah, Nuri; Al Furkan; Sumahiradewi, Luh Gede; Soraya, Indah (University of Prof. Dr. Hazairin, SH, 2024)
The Banggai Cardinal Fish (BCF) is a type of fish endemic to Indonesia whose distribution is very limited. This fish lives in shallow waters in the Banggai Islands (Central Sulawesi), especially in Banggai Laut Regency and Banggai Islands Regency. The purpose of this study was to find the optimal dose of trash fish feed for the growth of Cardinal Banggai (Petrapogon kauderni). This study used a completely randomized design (CRD) with a total of 4 treatments, namely P0 (0%, as control), P1 (5% trash fish feed), P2 (10% trash fish feed), P3 (15% trash fish feed), with replicated 3 times in each treatment. The data collected is primary data in the form of weight and length data, survival, feed conversion ratio, and water quality (temperature, salinity, pH, DO, ammonia). Based on research results, the best growth in weight and length is in the range of 10-15%, namely with a weight value of 0.003 grams/day and a length of 0.008 cm/day. The highest specific growth rate was P3 of 0.009%/day and the survival rate reached 70%. The lowest (best) average value of feed conversion ratio was at P2 at 0.49. While the quality of the water during the study was still in the optimal range for the proud cardinal fish, namely temperature 28-29 oC, salinity 30 ppt, pH 7.2—8.2, DO 4.0 mg/l, and ammonia 0.1 mg/l.